2009
DOI: 10.1111/j.1365-2486.2008.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal fire occurrence in Borneo over a period of 10 years

Abstract: South‐east Asia's tropical rainforests are experiencing the highest rate of deforestation worldwide and fire is one of the most important drivers of forest loss and subsequent carbon dioxide emissions. In this study, we analyzed all fire events in Borneo recorded by satellites over a period of 10 years. About 16.2 Mha, which corresponds to 21% of the land surface, have been affected by fire at least once and 6% more than one time. During El Niño conditions, which cause prolonged droughts in the region, the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(189 citation statements)
references
References 51 publications
6
180
0
3
Order By: Relevance
“…With sustainable peatland management, it would still be possible to maintain nearly half of all peatland areas in Kalimantan as PSF and thereby try to maintain the ecosystem functions and values, as well as prevent carbon emissions into the atmosphere. The most alarming feature of Kalimantan peatlands is the amount of unmanaged degraded peatland areas that have replaced forests typically destroyed by recurrent fires (Langner and Siegert 2009;Page et al 2009). In the majority of these areas, the original vegetation has been replaced by regrowth ranging from ferns to secondary forest.…”
Section: Discussionmentioning
confidence: 99%
“…With sustainable peatland management, it would still be possible to maintain nearly half of all peatland areas in Kalimantan as PSF and thereby try to maintain the ecosystem functions and values, as well as prevent carbon emissions into the atmosphere. The most alarming feature of Kalimantan peatlands is the amount of unmanaged degraded peatland areas that have replaced forests typically destroyed by recurrent fires (Langner and Siegert 2009;Page et al 2009). In the majority of these areas, the original vegetation has been replaced by regrowth ranging from ferns to secondary forest.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed peat fire occurrence in Borneo based on a fire hotspot database, spanning from January 1, 1997, to August 31, 2009, (21). As there is not a single sensor system which covers the full time period, a separate analysis for 2 investigation periods was carried out: (a) from 1997 to 2000 using fire hotspots from the Advanced Very High Resolution Radiometer (AVHRR) on board the National Oceanic and Atmospheric Administration (NOAA) satellite and from the Along-Track Scanning Radiometer (ATSR) on board the European Remote Sensing Satellite 2 (ERS-2), and (b) and from 2001 to 2009 using fire hotspots from the MODerate resolution Imaging Spectroradiometer (MODIS) on board the Terra and Aqua satellites (21,22). This fire hotspot time series showed that the peat fires in 2006 were the most severe after the well known 1997-1998 fire disaster.…”
Section: Resultsmentioning
confidence: 99%
“…22; http://maps.geog.umd.edu/firms/) to estimate the burned peat area for Indonesia. Previous studies showed that there is a reasonable correlation between burned areas deduced from MODIS hotspots and those derived from high resolution Landsat imagery, especially in peatlands, although a fire may cover the whole area of the sensor element (1 square km) or only a small fraction of it (12,21,32). When using hotspots to determine burned areas, several constrictions have to be kept in mind: (a) fires are only detected once or twice a day and thus rapidly spreading fires escape recording, (b) smoke from the fire often impedes the detection of hotspots, and (c) ground fires in tropical forests generally produce too little heat to be detected from space.…”
Section: Methodsmentioning
confidence: 99%
“…In a South East Asian context, ongoing deforestation threatens impending biodiversity losses in the region [43], a scenario that has already played out in Singapore [44]. Deforestation has been driven forward as a result of illegal logging activities that have been facilitated by corruption [45], and the logged forests become more susceptible to wild fires [46], which greatly amplify the negative effects of forest loss upon biodiversity. Moreover, the proliferation of oil palm plantations in South East Asia is placing tremendous pressure on forest cover [47,48].…”
Section: Discussionmentioning
confidence: 99%